Extrusive Luxation Injuries in Young Patients: A Retrospective Study with 5-Year Follow-Up - Enrico Spinas; Laura Pipi; Claudia Dettori (Dentistry Journal, 2020)
(1) Background: The purpose of this study was to analyze the influence of the chosen diagnostic and therapeutic approach (repositioning and splinting methods) on the risk, frequency and timing of the onset of pulp canal obliteration and pulp necrosis following extrusive luxation in young patients with permanent dentition. (2) Methods: From an initial sample of 50 subjects affected by extrusive luxation, were selected the clinical data of 13 patients presenting extrusive luxation but no other type of injury to the dental hard tissue. All teeth were examined according to a standardized protocol. Follow-up examinations were performed at regular intervals for 5 years. Statistical associations between pulp consequences and several covariates were assessed using the Mann–Whitney test and Fisher’s exact test. (3) Results: Among the 13 studied teeth, only 1 healed completely, whereas 9 showed pulp obliteration and 3 developed pulp necrosis. No tooth with obliteration developed pulp necrosis. The average time to treatment was 11.9 h. The treatment approaches used were manual repositioning, orthodontic repositioning and stabilization splinting. “Time to treatment” was the only covariate that showed a weak statistical association with the onset of pulp consequences. (4) Conclusions: There is still uncertainty over the most appropriate therapeutic approach to adopt in young patients with extrusive luxation injuries, particularly for repositioning of the injured tooth. Extruded teeth should be treated as soon as possible after the traumatic event. This study highlighted the value of orthodontic repositioning of the extruded tooth, which does not seem to aggravate the conditions of the dental pulp. In addition, the study confirmed that prophylactic endodontic treatment is not appropriate for immature teeth affected by extrusive luxation injuries, given the extreme rarity of pulp necrosis in teeth already affected by pulp obliteration.